Pendidikan yang Membebaskan - Reni, Siti; Asbari, Masduki; Ramadhan, Mohamad Biazt (Journal of Information Systems and Management (JISMA), 2024)
This article is a review which is a critical reading of a guidebook that inspires and provides motivation for readers entitled "Liberating Education" by Akhmad Muhaimin Azzet which reflects on the book "Education of the Oppressed" by Paulo Freire. In this book it has been explained that current education, according to Freire, is considered inhumane because it tends to view students as objects who must receive knowledge from educators as subjects. Freire argued that education should position students as active subjects in facing their social reality and experiencing freedom. Liberating education is not just filling students' empty glasses with knowledge, but providing education in accordance with students' development and potential so that they grow into independent human beings. Even though challenges such as inadequate school conditions still exist, enthusiasm and passion for working together in liberating education is still considered a major factor.